Weak measurements enhancing the quantum information facets of a driven Unruh–DeWitt detector - Xie, Jia-Ling; Zhu, Cheng-Jie; Tan, Jia; Hao, Xiang (Frontiers in Physics, 2025)
We developed a Hermitian operator representation of the Unruh channel for a driven accelerated detector in the presence of external noise. This representation is then used to provide a generalized analytical approach to a non-inertial evolution subjected to quantum weak measurements. The quantum information facets were then improved by performing weak measurements before and after the quantum channel. The external noise was modeled using a phase damping channel. The prominent oscillations of the quantum information are caused by vacuum fluctuations of the quantum fields coupled to the detector. Steady values are obtained for the quantum coherence and quantum Fisher information using the Unruh effect. Thus, quantum weak measurements can effectively suppress the decoherence induced by the relativistic acceleration. By comparing with cases without weak measurements, we demonstrate that there exist some regions with optimal measurement strengths that enhance the quantum coherence and quantum Fisher information. The effects of conditional improvement on the quantum information facets are still obvious in the presence of external noise.